(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the outcomes of intubation techniques in young adults suffering from nasolacrimal duct obstruction. Study Design: Experimental longitudinal study Place and Duration of Study: This study was conducted at the Ophthalmology Department, Post-Graduate Institute of Al-Ibrahim eye Hospital, Karachi, from May 2018 to November 2019. Materials and Methods: 136 patients aged 20-40 years were selected based on convenience sampling technique and divide into two groups, A in which silicon intubation was carried out, and Group B in which dacrocysto-rhinostomy (DCR) with silicon tube was carried out by the same surgeon. Success rate, recovery, complications, postoperative treatment, regurgitation, and the lacrimal duct's patency were the parameters taken under consideration. Data were analyzed using SPSS, with the independent t-test applied to assess the level of significance. Results: Significant difference (P value ≤0.01) was observed between Group A and B when it came to success rate and recovery. Other parameters such as complications, postoperative treatment, regurgitation, and patency of lacrimal duct were seen less in Group A as compared to Group B. Conclusion: The study concluded that silicon intubation is a better surgical procedure, showing better recovery and success rate and being more cost-effective with minimal trauma